Analysis of the Incidence of Euthyroid Sick Syndrome in Comprehensive Intensive Care Units and Related Risk Factors - Guo, Jianying; Hong, Yanyan; Wang, Zhiyong; Li, Yukun (Frontiers in Endocrinology, 2021)
Objective: Low plasma triiodothyronine (T3) concentration indicates nonthyroidal illness syndrome (NTIS), which might be associated with a poor outcome in patients in the intensive care unit (ICU). This study evaluated the relationship between NTIS and prognostic indicators in patients admitted to the ICU and examined the fT3 cut-offff points that could be associated with 28-day mortality. Methods: This prospective observational study included patients admitted to the ICU of The Third Hospital of Hebei Medical University from February to November 2018. The baseline variables and the occurrence of low free T3 (FT3) were collected. The patients were divided into the NTIS (FT3 < 3:28) and non-NTIS groups. We evaluated the relationship between NTIS and prognostic indicators in patients admitted to the ICU and examined the fT3 cut-offff points that could be associated with 28-day mortality. Results: Among 305 patients, 118 (38.7%) were in the NTIS group. FT3 (P < 0:001) and FT4 (P = 0:001) were lower, while the 28-day mortality rate (P < 0:001) and hospitalization expenses in ICU (P = 0:001) were higher in the NTIS group. The univariable analyses identifified NTIS, FT3, free thyroxine/FT3, APACHEII, sequential organ failure score, duration of mechanical ventilation, creatinine, oxygenation index, white blood cells, albumin, age, and brain natriuretic peptide as being associated with 28-day mortality (all P < 0:05). The cut-off value of FT3 for 28-day mortality was 2.88 pmol/L. The 28-day mortality rate and hospitalization expenses in the ICU were higher in patients with NTIS. NTIS was independently associated with 28-day mortality. Conclusion: This study presented that the incidence of ESS in the comprehensive ICU is 38.7%. APACHE II, SOFA, BNP, APTT, HGB, PLT, CREA, ALB, FT4, SBP, DBP are closely related to ESS, and BNP, PLT, ALB are independent risk factors for ESS.